Shoulder Pain in Policemen Due to Gun Hanging in Lahore, Pakistan - Shakeel, Hammad; Arooj, Ayesha; Tauqeer, Sana; Zakaullah, Iqra; Amin, Kinza; Saleem, Sidra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the frequency of shoulder pain in policemen due to gun hanging in Lahore, Pakistan. Study Design: Cross-Sectional Study. Place and Duration: Police Stations in Lahore, including Johar town, Model Town, Faisal Town and Khyaban e Amin. Lahore Pakistan from Nov 2019 to May 2020. Methodology: The data were collected from the policemen of different police stations in Lahore. Inclusion criteria were work-related shoulder pain and no fracture or dislocation, and with no history of trauma or injury, and the age limit is 25 to 40 years of policemen. Data was collected using "Shortened disabilities of the arm, shoulder and hand questionnaire (Quick DASH)". Results: There were 100 study participants. The mean age of the participants was 32.48±4.49 years. Results of this study showed that 43% had no shoulder pain, and 57% had shoulder pain due to gun hanging. In addition, results showed that 21% participants had no difficulty, 18% had mild difficulty, 27% had moderate difficulty, 22% had severe difficulty, and 12% were unable to open the jar. Conclusion: The shoulder pain due to gun hanging is high among policemen Daily life activities such as sleeping patterns and recreational and social life activities were also disturbed due to shoulder pain.